An Empirical Study of Factors Affecting Information Technology Projects Implementation - Ho, Koh Ming (1998)
Information Technology (IT) systems have much to offer in almost all sectors of industry and commence. Every year organizations make substantial investments of money and other resources into developing new information systems to meet their business operation requirements. Unfortunately, a significant amount of all Information Technology projects development undertaken is never completed or not used if completed (Kweku, Zbigniew 1994). There are many problems that have contributed to the failure of IT projects implementation. It is very easy to find negative examples or horror stories of IT implementation but some cases stand out precisely because things have gone right. The success and failures of IT projects implementation within an organization ultimately depends on several key factors. This study identified several major factors as contributing to the failure and success of IT implementation in two companies, a shipping and a telecommunication consortium located in the Klang Valley. This two-phase study first rank-ordered the three most common problems identified (quality, costs and time) in terms of its frequency of occurrences and then assessed the level of importance of the key factors grouped under the main areas of Organization & Management, Business Requirement, IT Investment and IT Infrastructure. The second phase then examined each of the key factors in the groups to determine the underlying interacting relationship associated with each other. A literature review of the key factors and previous research findings are presented. The results from this study is of great interest to the IS community in attempting to explain what issues or factors that might have contributed to the failure and success of IT project implementation.